PCR detection of Ganoderma spp. with translation elongation factor 1 - alpha (tef1-α) gene - Mohd Suhaimi, Nur Sofnis Erina (2017)
The most serious disease of oil palm in Malaysia all the while is basal stem rot (BSR). The losses can be accounted to about 50-85% over the life cycle of oil palm planting. There are several species of Ganoderma that are associated with BSR or isolated from oil palm trees but the major pathogen of this disease is Ganoderma boninense. The identification of Ganoderma species is difficult using morphological method. This will lead to a problem in disease management. The objectives of this study were 1) to extract genomic DNA from four Ganoderma species and 2) to develop a polymerase chain reaction (PCR) protocol using translation elongation factor 1-alpha (tef1-α) gene. To achieve objective 1, centrimethyl ammonium bromide (CTAB) method will be used for DNA extraction. To achieve objective 2, universal primers of tef1-α will be used to amplify Ganoderma species, sequenced the PCR products and identify the DNA sequences using Basic Local Alignment Search Tool (BLAST). For objective 1, only one genomic DNA species was obtained successfully with 295.0 ng/μl (A260/280) and the purity were 1.8 (A260/280) and 1.9 (A260/230). For objective 2, PCR protocol successfully amplified tef1-α gene for one species of Ganoderma. Primer pair tef1-α and ef1 could be used to amplify tef1-α gene from Ganoderma spp. even though it was successfully amplified only one species in this project which was Ganoderma boninense. PCR amplification will enable for better identification of Ganoderma species by improving DNA extraction and taking all the precautions.